Risk factors for the incidence and persistence of suicide-related outcomes: A 10-year follow-up study using the National Comorbidity Surveys - Borges, Guilherme (2007)
BACKGROUND: We report prospective associations of baseline risk factors with the first onset and persistence of suicide-related outcomes (SROs; ideation, plans, gestures, and attempts) over a 10-year interval among respondents who participated in both the 1990−02 National Comorbidity Survey (NCS) and the 2000−02 National Comorbidity Survey follow-up (NCS-2). METHODS: A total of 5001 NCS respondents were re-interviewed (87.6% of baseline sample) in the NCS-2. Three sets of baseline (NCS) risk factors were considered as predictors of the first onset and persistence of SROs: socio-demographics, lifetime DSM-III-R disorders, and SROs. RESULTS: New onsets included 6.2% suicide ideation, 2.3% plan, 0.7% gesture, and 0.9% attempts. More than one-third of respondents with a baseline history of suicide ideation continued to have suicide ideation at some time over the intervening decade. Persistence was lower for other SROs. The strongest predictors of later SROs were baseline SROs. Prospective associations of baseline mental disorders with later SROs were largely limited to the onset and persistence of ideation. LIMITATIONS: Although data were gathered prospectively, they were based on retrospective reports at both baseline and follow-up. CONCLUSIONS: Baseline history of SROs explained much of the association of mental disorders with later SROs. It is important clinically to note that many of the risk factors known to predict onset of SROs also predict persistence of SROs.